Machado-Joseph Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A 22-year-old male of Portuguese Azorean descent, presenting at age 16 years with postural instability and falls and developing severe generalized dystonia by age 20 years, is reported from the Center for Research in Neurodegenerative Diseases, University of Toronto, Ontario, Canada.